E-reading in Poland: Challenges and problems in new business models, public policies and copyright - Biga, Bartłomiej (Journal of Public Governance, 2016)
The aim of this paper is to analyze the economic impact of popularization of books in the electronic format. The text contains an analysis of challenges and problems in three key areas: business models, public policies, and copyright. On this basis, it is possible to establish strategies to minimize the negative effects of the recent developments and to make good use of new opportunities.